Nuns and the Effects of Catholic Schools: Evidence from Vatican II - Rania Gihleb; Osea Giuntella (Institute for the Study of Labor (IZA), 2013)
This paper examines the causal effects of Catholic schooling on educational attainment. Using a novel instrumental-variable approach that exploits an exogenous shock to the Catholic school system, we show that the positive correlation between Catholic schooling and student outcomes is explained by selection bias. Spearheaded by the universal call to holiness and the opening to lay leadership, the reforms that occurred at the Second Vatican Council (Vatican II) in the early 1960s produced a dramatic exogenous change in the cost/benefit ratio of religious life in the Catholic Church. The decline in vocations that followed contributed to a significant increase in costs and, in many cases, to the closure of Catholic schools. We document that this decline was heterogeneous across US dioceses, and that it was more marked in those dioceses governed by a liberal bishop. Merging diocesan data drawn from the Official Catholic Directory (1960-1980) and the US Census, we show that that the variation in the supply of female religious teachers across US dioceses is strongly related to Catholic schooling. Using the abrupt decline in female vocations as an instrument for Catholic schooling, we find no evidence of positive effects on student outcomes.
Keywords: I20; J24; N3; 330; Catholic schools; instrumental variable; selection